Determinação voltamétrica de hidrocarbonetos policíclicos aromáticos e de aminas biogências em alimentos - Costa, Daniel Jackson Estevam da (2017)
Polycyclic aromatic hydrocarbons (PAHs) are toxic substances and are considered mutagenic and carcinogenic. Among the several analytical techniques developed for the monitoring of these analytes, the chromatography stands out. In this work, voltammetric methods were used for the determination of benzo (a) pyrene, pyrene and fluoranthene HPAs, using the carbon glass electrode (CGE) with and without modification of carbon nanotubes and carbon paste electrodes (CPE) modified with metal phthalocyanines in acetate buffer (pH 4.0). The electrochemical study showed that these HPAs present only one oxidative process, in different potentials EP(benzo(a)pyrene) ≈ 0.95V, EP(pyrene) ≈ 1.03V and EP(fluoranthene) ≈ 1.35V. Therefore, differential pulse voltammetry (DPV) methods were developed for the simultaneous determination of PAHs using surfactant sodium dodecyl sulfate (SDS), which facilitated a better interaction between the electrodes and the analyte. Other toxic organic compounds found in foods are biogenic amines (BAs), these compounds are naturally found in humans and many are important for the proper functioning of the body, however, daily consumption of these compounds cause serious toxicological effects, undesirable for health it is found that some may react with other compounds and become carcinogenic. Similar to PAHs, the main technique used is chromatography. In the second part of this work, voltammetric methods were used to determine the ABs (tryptamine, histamine, putrescine, cadaverine and 2phenylethylamine) in GCE and the boron doped diamond electrode (BDDE). However, tryptamine in GCE was the only one that presented an electrochemical response, and a voltammetric methodology was developed to determine this BA in food. Tryptamine presents two oxidative processes EP1 ≈ 0.85V and EP2 ≈ 1.25V, with P1 being the most sensitive and its response was used for the construction of an electroanalytical method using square wave voltammetry (SWV) in acetate buffer showing a linear response range of (4.7 to 54.5) × 10-8 mol L-1, low limit of detection (0.8 × 10-9 mol L-1) and limit of quantification (2.7 × 10-9 mol L-1), the tryptamine content was determined in bananas, tomatoes, gorgonzola) and sausages (chicken sausage and calabresa), obtaining recoveries above 90%. In the BDDE, the BAs presented electrochemical response, at different potentials, resulting in their simultaneous determination in DPV using acetate buffer (pH 5.0), the method was applied satisfactorily in food: banana, tomato and cheese muzzarela, obtaining recoveries above 90 %.